El sistema general de participaciones en el proceso de descentralización fiscal en Colombia (2017)
With the Political Constitution of 1991, a guiding norm for the distribution of resources and powers was officially established among the different levels of government, which allowed strengthening the process of fiscal decentralization in the country. However, the transfer settlement base initially proposed was modified through constitutional reforms materialized in the Legislative Acts 01 of 2001, and 04 of 2007 that created and consolidated the General System of Participation (SGP in Spanish), respectively. From these reforms emerged elements of discussion that are important to debate from the perspective of the academy, which is why it is appropriate to raise a study which purpose is to determine the role played by the (GSP) in the country´s fiscal decentralization process.